Drivers Of Domestic Waste Separation Intentions at The Household Level: An Application of The Theory of Planned Behavior - Dr. Emily Chen; Prof. Jacob Mensah (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
Effective domestic waste separation at the source is a cornerstone of sustainable waste management, yet its implementation faces significant challenges globally, particularly at the household level. This article investigates the determinants of household intention to separate domestic waste, applying Ajzen's Theory of Planned Behavior (TPB) as the guiding theoretical framework. The TPB posits that an individual's intention to perform a behavior is influenced by their attitude towards the behavior, subjective norms, and perceived behavioral control. Through a comprehensive review of existing literature, this study synthesizes findings on how these constructs, alongside other contextual factors, influence household waste separation intentions. Understanding these drivers is crucial for designing targeted interventions and policies that promote greater participation in waste segregation programs, ultimately contributing to improved resource recovery and reduced environmental impact.